2015
DOI: 10.1073/pnas.1508220112
|View full text |Cite
|
Sign up to set email alerts
|

A lipid switch unlocks Parkinson’s disease-associated ATP13A2

Abstract: ATP13A2 is a lysosomal P-type transport ATPase that has been implicated in Kufor-Rakeb syndrome and Parkinson's disease (PD), providing protection against α-synuclein, Mn 2+ , and Zn 2+ toxicity in various model systems. So far, the molecular function and regulation of ATP13A2 remains undetermined. Here, we demonstrate that ATP13A2 contains a unique N-terminal hydrophobic extension that lies on the cytosolic membrane surface of the lysosome, where it interacts with the lysosomal signaling lipids phosphatidic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
113
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 37 publications
7
113
0
Order By: Relevance
“…The cellular functions of PI (3,5)P2 might partially relate to ATP13A2, since loss of ATP13A2 results in neurodegeneration, an increased lysosomal pH and impaired autophagy. 2 We further show that ATP13A2 mediates protection against rotenone-induced mitochondrial stress requiring both catalytic activity of ATP13A2 and the lipids PA and PI (3,5)P2. This hints to a lipiddependent activation of ATP13A2 that is important for mitochondrial homeostasis and/or clearance 2 (Fig.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…The cellular functions of PI (3,5)P2 might partially relate to ATP13A2, since loss of ATP13A2 results in neurodegeneration, an increased lysosomal pH and impaired autophagy. 2 We further show that ATP13A2 mediates protection against rotenone-induced mitochondrial stress requiring both catalytic activity of ATP13A2 and the lipids PA and PI (3,5)P2. This hints to a lipiddependent activation of ATP13A2 that is important for mitochondrial homeostasis and/or clearance 2 (Fig.…”
mentioning
confidence: 59%
“…However, we demonstrated that the N-terminus does not traverse the membrane, but rests on the cytosolic membrane surface of late endo-/lysosomes where it may serve as a docking platform for lipids and proteins 2 (Fig. 1).…”
mentioning
confidence: 89%
See 3 more Smart Citations